Dynamic modeling for apartment brand management in the housing market - Choi, Minji; Park, Moonseo; Lee, Hyun-Soo; Hwang, Sungjoo (International Journal of Strategic Property Management, 2017)
A company’s brand can be considered its most valuable asset. The known impact of branding has inspired a number of Korean construction companies to initiate a new marketing strategy, apartment branding, in the competitive market since the 1990s. As a result, the market-leading brands had stronger sales performances over non-branded apartments in the same residential district. However, major companies with well-known apartment brands still face challenges in managing brand equity constructs, particularly brand loyalty, due to the distinctive characteristics of constructed products (i.e., durability and costliness). To address this issue, this research develops qualitative system dynamics models to analyze the core mechanisms and problems of apartment brand equity building process and proposes long-term managerial strategies to overcome the problem of obtaining apartment brand loyalty. The research outcome is expected to support the strategic decision-making processes of apartment brand managers and to provide implications for further branding applications in other metropolitan areas anticipating a sharp increase in apartments.